Pendidikan Manajemen Inklusif Merupakan Salah Satu Alternatif Mengatasi Permasalahan Sosial Anak Berkebutuhan Khusus Atau Disabilitas - Opi Andriani; Ana Imelia Mursyida; Mutaharah Mutaharah; Wilda Hayati (Institut Nalanda, 2024)
This article aims to describe inclusive management, techniques for collecting data through qualitative methods which emphasize analysis or descriptiveness. The research results show that: (1) In terms of optimizing the management of inclusive education, the roles of the government, school principals, teachers and parents are the most important. (2) there are many inhibiting factors in the process of implementing inclusion management, one of which is the availability of internal special educators who handle children with special needs and inclusion. In previous years, there was only 1 teacher. (3) One of the school's initiatives, apart from relying on the presence of external forums, is that the school holds training and provision internally.